From Noosphere to Omega Point: Pierre Teilhard de Chardin and the Foundations of Cosmic Post-Secular Theology - Nana Supiana; Muhammad Yusuf Wibisono (Parahyangan Catholic University, 2026)
This study analyzes the relevance of Pierre Teilhard de Chardin’s thought through the concepts of the noosphere, Christogenesis, and the Omega Point within the frameworks of progressive theology, evolutionary mysticism, and post-secularism. The study responds to the growing need for a theological framework capable of bridging the relationship between religion, science, technology, and contemporary ecological crises. The research employs a qualitative approach using the Systematic Literature Review (SLR) method based on the PRISMA guidelines. The study collected data from academic publications indexed in Scopus and Google Scholar, focusing primarily on literature published between 2020 and 2025 while also incorporating earlier works with significant theoretical relevance. The findings reveal three major conclusions. First, contemporary scholarship increasingly positions Teilhard as a progressive theologian who integrates faith and science through the concepts of cosmic evolution and Christogenesis. Second, the concepts of the noosphere, Christogenesis, and the Omega Point form a framework of evolutionary mysticism that connects spirituality, collective consciousness, and ecological responsibility within a single cosmic horizon. Third, within the post-secular context, Teilhard’s thought offers a model of religiosity that reconciles scientific rationality, technological development, and the search for spiritual meaning in modern society. This study contributes to the development of ecological theology, technology ethics, religious education, and dialogue between religion and science. The originality of this study lies in its conceptual synthesis that integrates progressive theology, evolutionary mysticism, and the post-secular paradigm within a single analytical framework. Based on this synthesis, the study proposes the concept of Cosmic Post-Secular Theology as a theoretical contribution for understanding the relevance of religion amid contemporary ecological transformation, technological advancement, and changing forms of religiosity.